Pengaruh Karakteristik Sosial Ekonomi Konsumen terhadap Preferensi dalam Membeli Ayam Lokal di Pasar Ciseeng Kecamatan Ciseeng Kabupaten Bogor - Aisya Rizqi Fadhila; Hasni Arief; Lilis Nurlina Lilis Nurlina (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Local chicken is a livestock commodity that has experienced a population increase in Bogor District over the past five years, indicating a growing demand for local chicken products. Consumers have various reasons for purchasing local chicken. Consumers with different characteristics and backgrounds will also have different preferences. Based on its conditions, this study aims to determine consumer characteristics and preferences, and analyze the influence of consumer socioeconomic characteristics on their purchasing preferences for local chicken. The study was conducted in July 2024 at Ciseeng Market, Ciseeng Subdistrict, Bogor District. This study employed a quantitative approach, utilizing a survey method (sampling) as the data collection technique. The sampling technique used was accidental sampling, resulting in a sample size of 100 respondents for this study. The data analysis methods employed were descriptive analysis, Importance-Performance Analysis (IPA), and Multinomial Logistic Regression analysis. The study's results indicated that consumers who prefer local chicken at Ciseeng Market have socioeconomic characteristics in the late adult category, with a high school education level, a family size of 1-4 people, and an income of more than Rp3,500,000/month. The IPA analysis revealed that the attribute of price discounts primarily drove consumer preference for local chicken. Offering discounts to consumers can be an effective strategy for boosting sales and attracting new customers. The attributes, including the price of local chicken, weight, type of cut, producer attention, and freshness of the chicken, fall into the maintain performance quadrant. The influence of consumer socioeconomic characteristics on their preferences in purchasing local chicken, analyzed by multinomial logistic regression, showed that the characteristics of age, education, number of family members, and income have a positive and significant effect on consumer preference for local chicken, although only partially significant for the variables of education and number of family members.